2014
DOI: 10.1097/imi.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Can the Learning Curve of Totally Endoscopic Robotic Mitral Valve Repair be Short-Circuited?

Abstract: Objective A concern with the initiation of totally endoscopic robotic mitral valve repair (TERMR) programs has been the risk for the learning curve. To minimize this risk, we initiated a TERMR program with a defined team and structured learning approach before clinical implementation. Methods A dedicated team (two surgeons, one cardiac anesthesiologist, one perfusionist, and two nurses) was trained with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…According to articles A5, A10, A11 and A15, in the intraoperative period, the nurse is responsible for guiding the robotic device for the cart of the patient, performed under the guidance of the surgeon (13,20,(22)(23) . The setting and preparation of the robot for surgery includes the connection of all necessary pieces, such as sterile wrappings and necessary connectors, as well as the calibration process (23) .…”
Section: Transoperative/intraoperativementioning
confidence: 99%
See 2 more Smart Citations
“…According to articles A5, A10, A11 and A15, in the intraoperative period, the nurse is responsible for guiding the robotic device for the cart of the patient, performed under the guidance of the surgeon (13,20,(22)(23) . The setting and preparation of the robot for surgery includes the connection of all necessary pieces, such as sterile wrappings and necessary connectors, as well as the calibration process (23) .…”
Section: Transoperative/intraoperativementioning
confidence: 99%
“…Regarding the preoperative period, seven articles (A1, A2, A3, A4, A5, A7, A9) mentioned the importance of an adequate training both for the nurse and for the entire surgical staff (5,(16)(17)(18)(19)(20)(21) . A training program for nurses allow that the professionals acquire competence and safety on the practice of care, reducing the risks for patients and contributing for positive results in nursing care (21) .…”
Section: Preoperativementioning
confidence: 99%
See 1 more Smart Citation
“…For MIMVR programmatic success, it is imperative to develop a stable team and a graduated learning pathway. 28 Team failure is multifactorial and can result from poor patient selection, inadequate mitral procedural volume, too rapid a progression toward robotics, inconsistent tableside surgical assistance, limited experience with TEE, and inadequate support from the hospital or cardiology department.…”
Section: Stepwise Learningmentioning
confidence: 99%
“…The clinical trials reported have demonstrated that telesurgery is feasible for assisting and/or mentoring by an expert, and remote teaching of simple procedures such as endoscopy [23]. Additionally, it is recommended that telesurgery should only be performed after considerable instruction and practice using the telesurgical systems involved [24,25]. This can be accomplished via a virtual surgical training simulator, cadavers, animal laboratory, or a mixture of all three [24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%